2023
DOI: 10.3847/2041-8213/acffc5
|View full text |Cite
|
Sign up to set email alerts
|

Dissonance in Harmony: The UV/Optical Periodic Outbursts of ASASSN-14ko Exhibit Repeated Bumps and Rebrightenings

Shifeng Huang,
Ning Jiang,
Rong-Feng Shen
et al.

Abstract: ASASSN-14ko was identified as an abnormal periodic nuclear transient with a potential decreasing period. Its outbursts in the optical and UV bands have displayed a consistent and smooth “fast rise and slow decay” pattern since its discovery, which has recently experienced an unexpected alteration in the last two epochs, as revealed by our proposed high-cadence Swift observations. The new light curve profiles show a bump during the rising stages and a rebrightening during the declining stages, making them much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In contrast, the pTDE candidate ASASSN-14ko recently showed noticeable bumps before the main UV/ optical peaks and rebrightenings after that. This can be interpreted as a consequence of the collision between the stream debris and the extended disk in the pTDE scenario (Huang et al 2023b), which distinguishes it from AT 2023lli and other TDEs.…”
Section: Comparison With Bumps In Other Tdesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the pTDE candidate ASASSN-14ko recently showed noticeable bumps before the main UV/ optical peaks and rebrightenings after that. This can be interpreted as a consequence of the collision between the stream debris and the extended disk in the pTDE scenario (Huang et al 2023b), which distinguishes it from AT 2023lli and other TDEs.…”
Section: Comparison With Bumps In Other Tdesmentioning
confidence: 99%
“…Most TDEs that have been discovered so far exhibit a smooth single-peak light curve in both UV and optical bands. However, some of them display a bump in the rising phase of their light curves (Holoien et al 2019;Charalampopoulos et al 2023;Faris et al 2023;Huang et al 2023b;Wang et al 2023b;Z. Lin et al 2024, in preparation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASASSN-14ko (Holoien et al 2014a) is another nuclear transient with a bump reported in its rising phase (Huang et al 2023). However, it displays spectra more similar to those of AGNs (Payne et al 2021) and periodicity in its outbursts (Payne et al 2021(Payne et al , 2022(Payne et al , 2023, which are not seen in the class of TDEs to which AT 2019azh belongs.…”
Section: Early Light-curve Structurementioning
confidence: 99%
“…Alternatively, multiple independent TDEs could be supported by an enhanced TDE rate due to the concentrated nuclear stellar profile, e.g., in post-starburst galaxies (e.g., Arcavi et al 2014;Hammerstein et al 2021;Bortolas 2022;Wang et al 2024) or galaxies with nuclear star clusters (Pfister et al 2020). Despite the challenges, several candidates for repeated pTDE have been reported, e.g., IC 3599 (Campana et al 2015), ASASSN-14ko (Payne et al 2021, 2022, 2023Huang et al 2023), Swift J023017.0+283603 (Evans et al 2023;Guolo et al 2024b), eRASSt J045650.3-203750 (Z. Liu et al 2023, AT 2018fyk (Wevers et al 2023;Pasham et al 2024), RX J133157.6-324319.7 (Hampel et al 2022Malyali et al 2023), and AT 2020vdq (Somalwar et al 2023b). The great diversity of the flaring intervals, bands, and shapes (listed in Table 2) among these sources calls for additional theoretical efforts.…”
Section: Introductionmentioning
confidence: 99%